Strengthening the Image of Musholla through Strategic Marketing and Effective Volunteer Human Resource Management - Irmal; Syahnego; Rian Sri Rahayu (Simfoni Ilmu Cindekia, 2025)
Musholla plays a strategic role not only as a place of worship but also as a center for religious and social activities in the community. However, many musholla still face challenges in building a positive image and encouraging active community participation. This community service program aimed to enhance the image of a local musholla by implementing effective marketing strategies and improving the capacity of volunteer human resources. The methods included problem identification through focus group discussions, training in both digital and offline marketing strategies, and workshops on volunteer management. The results showed increased awareness among musholla managers and volunteers about the importance of digital branding and improved skills in organizing programs professionally. This program contributes to transforming the musholla into an inclusive and vibrant center of worship and social empowerment.